Constitutive activation of DIA1 (DIAPH1) via C‐terminal truncation causes human sensorineural hearing loss. Issue 11 (5th October 2016) - Ueyama, Takehiko; Ninoyu, Yuzuru; Nishio, Shin‐ya; Miyoshi, Takushi; Torii, Hiroko; Nishimura, Koji; Sugahara, Kazuma; Sakata, Hideaki; Thumkeo, Dean; Sakaguchi, Hirofumi; Watanabe, Naoki; Usami, Shin‐ichi; et al.
Abstract: DIAPH1 encodes human DIA1, a formin protein that elongates unbranched actin. The c.3634+1G>T DIAPH1 mutation causes autosomal dominant nonsyndromic sensorineural hearing loss, DFNA1, characterized by progressive deafness starting in childhood. The mutation occurs near the C‐terminus of the diaphanous autoregulatory domain (DAD) of DIA1, which interacts with its N‐terminal diaphanous inhibitory domain (DID), and may engender constitutive activation of DIA1. However, the underlying pathogenesis that causes DFNA1 is unclear. We describe a novel patient‐derived DIAPH1 mutation (c.3610C>T) in two unrelated families, which results in early termination prior to a basic amino acid motif (RRKR 1204–1207 ) at the DAD C‐terminus. The mutant DIA1(R1204X) disrupted the autoinhibitory DID‐DAD interaction and was constitutively active. This unscheduled activity caused increased rates of directional actin polymerization movement and induced formation of elongated microvilli. Mice expressing FLAG‐tagged DIA1(R1204X) experienced progressive deafness and hair cell loss at the basal turn and had various morphological abnormalities in stereocilia (short, fused, elongated, sparse). Thus, the basic region of the DAD mediates DIA1 autoinhibition; disruption of the DID‐DAD interaction and consequent activation of DIA1(R1204X) causes DFNA1. Synopsis: A novel clinical DIAPH1 mutation (c.3610C>T) is found in two unrelated families, resulting in a constitutively active DIA1. Patients and mice expressing the DIA1(R1204X) protein show progressive hearing loss beginning in the high‐frequency range and mimicking a novel DFNA1 subtype. A novel DIAPH1 mutation results in early termination of DIA1 at the diaphanous autoregulatory domain (DAD), R1204X. DIA1(R1204X) disrupts the diaphanous inhibitory domain (DID)–DAD interaction and is constitutively active. Mice expressing DIA1(R1204X) show progressive deafness and OHC loss at the basal turn. DIA1(R1204X) causes a novel DFNA1 subtype showing progressive hearing loss beginning in the high‐frequency range and in childhood. Abstract : A novel clinical DIAPH1 mutation (c.3610C>T) is found in two unrelated families, resulting in a constitutively active DIA1. Patients and mice expressing the DIA1(R1204X) protein show progressive hearing loss beginning in the high‐frequency range and mimicking a novel DFNA1 subtype.